Clinical Pharmacology and Pharmacokinetics of Levetiracetam - Wright, Chanin C.; Downing, Jana; Mungall, Diana; Khan, Owais; Williams, Amanda; Fonkem, Ekokobe; Garrett, Darin; Aceves, Jose; KIRMANI, BATOOL F. (Frontiers in Neurology, 2013)
Status epilepticus and acute repetitive seizures still pose a management challenge despite the recent advances in the field of epilepsy. Parenteral formulations of old anticonvulsants are still a cornerstone in acute seizure management and are approved by the FDA. Intravenous levetiracetam, a second generation anticonvulsant, is approved by the FDA as an adjunctive treatment in patients 16 years or older when oral administration is not available. Data have shown that it has a unique mechanism of action, linear pharmacokinetics and no known drug interactions with other anticonvulsants. In this paper, we will review the current literature about the pharmacology and pharmacokinetics of intravenous levetiracetam and the safety profile of this new anticonvulsant in acute seizure management of both adults and children.